Patterns of liver injury in COVID-19 – a German case series. Issue 7 (August 2020) - Schattenberg, Jörn M; Labenz, Christian; Wörns, Marcus-Alexander; Menge, Philipp; Weinmann, Arndt; Galle, Peter R; Sprinzl, Martin F.
Background: Reports of liver injury in patients with novel coronavirus disease 2019 (COVID-19) are emerging from China and the USA. A wide variety of liver function test abnormalities and few cases of severe liver failure have been reported. No data on the hepatic phenotype from Europe are available at current. Methods: We report a case series of 44 consecutive patients hospitalized for COVID-19 in Germany. Results: At the time of admission, aspartate aminotransferase greater than the upper limit of normal was present in 70%, while alanine aminotransferase was elevated in 15.8%. Markers of cholestatic liver injury were altered only in a minority of patients. During hospitalization, 31% and 22% experienced increasing aspartate aminotransferase and alanine aminotransferase, respectively, when transaminases were normal at admission. Severe liver injury defined by 3×> upper limit of normal was observed in 9.1% over a mean time of 10.5 days. Importantly, patients exhibited cytotoxicity including lactate dehydrogenase and creatinine kinase elevations, but no signs of relevant liver function impairment. Conclusion: In summary, in a case series of hospitalized patients in Germany, cytotoxicity in the absence of severe liver dysfunction at admission and only few cases suggestive of severe liver injury during hospital were observed.